Recalcitrant crusaders? : the relationship between Southern Italy and Sicily, crusading and the crusader states, c. 1060-1198 /: the relationship between Southern Italy and Sicily, crusading and the crusader states, c. 1060-1198. (2020) - Hailstone, Paula Z
No abstract available